Competing interests during the key N-glycosylation of 6-chloro-7-deaza-7-iodopurine for the synthesis of 7-deaza-2′-methyladenosine using Vorbrüggen conditions - Naciuk, Fabrício Fredo; Nascimento, Andrey Fabricio Ziem; Rocha, Rebeca Paiva Froes; Rustiguel, Joane Kathelen; Coimbra, Lais Durço; Marques, Rafael Elias; Bruder, Marjorie (Frontiers in Chemistry, 2023)
The nature of a major by-product formed during the N-glycosylation of 6-chloro-7-deaza-7-iodopurine with perbenzoylated 2-methyl-ribose under Vorbrüggen conditions was investigated. Spectroscopic analyses support that the solvent itself is converted into a nucleophilic species competing with the nucleobase and further reacting with the activated riboside in an unanticipated fashion. These findings call for a revision of reaction conditions when working with weakly reactive nucleobases in the presence of Lewis acids. This work ultimately proposes a short 3-step synthesis of the antiviral agent 7DMA from commercial precursors and presents preliminary results of efficacy against an emerging flavivirus in vitro.